Hemodynamic changes in hepatic sinusoids of hepatic steatosis mice - Fan, Jing (World J Gastroenterol, 2019)
BACKGROUND: Fatty liver (FL) is now a worldwide disease. For decades, researchers have been kept trying to elucidate the mechanism of FL at the molecular level, but rarely involve the study of morphology and medical physics. Traditionally, it was believed that hemodynamic changes occur only when fibrosis occurs, but it has been proved that these changes already show in steatosis stage, which may help to reveal the pathogenesis and its progress. Because the pseudolobules are not formed during the steatosis stage, this phenomenon may be caused by the compression of the liver microcirculation and changes in the hemodynamics. AIM: To understand the pathogenesis of hepatic steatosis and to study the hemodynamic changes associated with hepatic steatosis. METHODS: Eight-week-old male C57BL/6 mice were divided into three groups randomly (control group, 2-wk group, and 4-wk group), with 16 mice per group. A hepatic steatosis model was established by subcutaneous injection of carbon tetrachloride in mice. After establishing the model, liver tissue from mice was stained with hematoxylin and eosin (HE), and oil red O stains. Blood was collected from the angular vein, and hemorheological parameters were estimated. A two-photon fluorescence microscope was used to examine the flow properties of red blood cells in the hepatic sinusoids. RESULTS: Oil red O staining indicated lipid accumulation in the liver after CCl(4) treatment. HE staining indicated narrowing of the hepatic sinusoidal vessels. No significant difference was observed between the 2-wk and 4-wk groups of mice on morphological examination. Hemorheological tests included whole blood viscosity (mPas, γ = 10 s-(1)/γ = 100 s(-1)) (8.83 ± 2.22/4.69 ± 1.16, 7.73 ± 2.46/4.22 ± 1.32, and 8.06 ± 2.88/4.22 ± 1.50), red blood cell volume (%) (51.00 ± 4.00, 42.00 ± 5.00, and 40.00 ± 3.00), the content of plasma fibrinase (g/L) (3.80 ± 0.50, 2.90 ± 0.80, and 2.30 ± 0.70), erythrocyte deformation index (%) (44.49 ± 5.81, 48.00 ± 15.29, and 44.36 ± 15.01), erythrocyte electrophoresis rate (mm/s per V/m) (0.55 ± 0.11, 0.50 ± 0.11, and 0.60 ± 0.20), revealing pathological changes in plasma components and red blood cells of hepatic steatosis. Assessment of blood flow velocity in the hepatic sinusoids with a laser Doppler flowmeter (mL/min per 100 g) (94.43 ± 14.64, 80.00 ± 12.12, and 67.26 ± 5.92) and two-photon laser scanning microscope (μm/s) (325.68 ± 112.66, 213.53 ± 65.33, and 173.26 ± 44.02) revealed that as the modeling time increased, the blood flow velocity in the hepatic sinusoids decreased gradually, and the diameter of the hepatic sinusoids became smaller (μm) (10.28 ± 1.40, 6.84 ± 0.93, and 5.82 ± 0.79). CONCLUSION: The inner diameter of the hepatic sinusoids decreases along with the decrease in the blood flow velocity within the sinusoids and the changes in the systemic hemorheology.